Utilization of Cull Vegetables as Feedstuffs for Cattle - Courtney Davis; Lindsey Wiggins; Matt Hersom (EDIS, 2012)
Cull vegetables can be an economical source of nutrients in beef cattle diets. They may be offered to beef cattle producers at a decreased cost or no cost. This 3-page fact sheet discusses the nutrient content and characteristics that need to be understood when utilizing cull vegetables. Written by Courtney Davis, Lindsey Wiggins, and Matt Hersom, and published by the UF Department of Animal Sciences, August 2012.